2015
DOI: 10.1155/2015/973973
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Structure, Oxygen-Transporting Functions, and Ionic Composition of Erythrocytes at Vascular Diseases

Abstract: The present paper explores the role of erythrocytes in the pathogenesis of vascular diseases. The state of erythrocytes, their ionic composition and structure, and properties of erythrocytes hemoglobin were studied by using laser interference microscopy, Raman scattering spectroscopy, and capillary electrophoresis. In patients suffering from vascular disorders we identified statistically significant changes in the shape of erythrocytes, their ionic composition, and redistribution of hemoglobin throughout cells. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Changes in the phospholipid and fatty-acid composition of the erythrocyte lipids indicate structural rearrangements in the membrane of erythrocytes and thus, point to the functional changes affecting the erythrocytes in general, as well as the primary oxygen-transport protein of erythrocytes, Hb (membrane-bound and cytoplasmic form) [6,11]. In addition, changes in the functional and morphological properties of Hb and erythrocytes in general can throw light on the degree and the nature of the pathological process accompanied by hypoxia.…”
Section: Effect Of Hypoxia On the Fatty-acid Composition Of Erythrocymentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the phospholipid and fatty-acid composition of the erythrocyte lipids indicate structural rearrangements in the membrane of erythrocytes and thus, point to the functional changes affecting the erythrocytes in general, as well as the primary oxygen-transport protein of erythrocytes, Hb (membrane-bound and cytoplasmic form) [6,11]. In addition, changes in the functional and morphological properties of Hb and erythrocytes in general can throw light on the degree and the nature of the pathological process accompanied by hypoxia.…”
Section: Effect Of Hypoxia On the Fatty-acid Composition Of Erythrocymentioning
confidence: 99%
“…Different pathologies cause changes in the amount, distribution and conformation of Hb [4][5][6][7]. Many pathological states are accompanied by development of hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the phospholipid and FA composition of the erythrocyte lipids point to structural rearrangements in the membrane of erythrocytes and thus to the functional changes on the part of the erythrocyte as a whole, as well as on the part of the primary oxygen-transport protein of RBCs -haemoglobin (membrane-bound and cytoplasmic form) [4,5]. Our data obtained by RS suggested that these changes are linked to disruption of the conformation of haemoglobin and primarily its heme structures.…”
Section: Changes In the Oxygen-binding Capacity Of Erythrocyte Haemogmentioning
confidence: 65%
“…Many studies [1][2][3], including ours [4][5][6], have provided evidence that the lipid phase plays an active role in the regulation of the oxygen-transport function of haemoglobin during hypoxia, which is the cause and consequence of many cardiovascular diseases [7]. However, the human body often faces a situation when in some tissues and, in particular, in the blood, there may be an excessive amount of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…The use of Raman spectroscopy (RS) made it possible to identify changes in the conformation of hemoporphyrin in patients with severe arterial hypertension and under the therapeutic interval hypoxia in patients with stable effort [4] and in patients with circulatory failure [57]. …”
Section: Introductionmentioning
confidence: 99%